QUANTITATIVE RISK ASSESSMENT AND FATIGUE ANALYSIS OF UNPROTECTED BURIED GAS PIPELINE CROSSED BY HEAVY VEHICLE. CASE STUDY: USING OF GAS PIPELINE INSPECTION ROAD AS COAL TRANSPORTATION - MARIZ ARIEF (NIM : 23108029); Pembimbing : Prof. Dr. Ir. IGN Wiratmaja Puja, TRIA
Gas pipelines have a very important role in the ransportation of natural gas. Materials of natural gas that could pose a hazard and have significant consequences on society, environment and business, requires its operators to take precautions to prevent such unwanted event. Through risk analysis can be known the level of risk and found ways to overcome a dangerous disaster. The factors causing the accident can be estimated by doing the risk assessment. At present the factors causing the accident on the largest pipeline is the third party activities encroach to the pipeline. In this thesis conducted an analysis of the influence of transportation activity plan that encroach to the gas pipeline. Analysis is performed to determine the level of risk and several reduction measures. Analysis were performed with the method of QRA (Quantitative Risk Assessment) by using BS PD 8010-3: 2009 and API RP 581 as guidelines. In addition it also conducted the analysis of fatigue due to the influence of vehicle weight and its trips. In the case study of using gas pipeline inspection road as coal transportation, there are several gas pipelines influenced by this coal transportation, but in the analysis, only one pipeline that is quite critical (24-inch gas pipeline) is to be analyzed. The sensitive parameters to the calculation of fatigue is the pipeline burial depth which is directly proportional to the fatigue life. D/t ratio is inversely proportional to the fatigue life. Internal pressure is sensitive at the low pressure, while at high pressure, 52 bars (750 psi) or more, is not too sensitive and it is inversely proportional to fatigue life. The primary factor affecting the QRA gas pipelines at the road crossing is an external interference. In the case study of using gas pipeline inspection road as coal transportation, fatigue life result is 20.5 years with additional transportation. QRA results for the existing condition of the gas pipeline is at an acceptable level with individual risk of 1.26x10-7 events/year and the societal risk of 9.27x10-5 fatalities/year. While the coal transportation activity begin, an individual risk increase to 2.5x10-3 events/year and the societal risk to 3.49x10-1 fatalities/year and in unacceptable levels. The addition of a suitable concrete slab, in this case with dimension of 2 x 2 meters with a minimum thickness of 20 cm can reduce the level of risk to the tolerable if ALARP condition. The value of an individual risk to be 7.3x10-6 events/year and social risks to 1.11x10-3 fatalities/year.